Neuron-specific spinal cord translatomes reveal a neuropeptide code for mouse dorsal horn excitatory neurons - Rebecca Rani Das Gupta (Nature Portfolio, 2021)
Abstract The spinal dorsal horn harbors a sophisticated and heterogeneous network of excitatory and inhibitory neurons that process peripheral signals encoding different sensory modalities. Although it has long been recognized that this network is crucial both for the separation and the integration of sensory signals of different modalities, a systematic unbiased approach to the use of specific neuromodulatory systems is still missing. Here, we have used the translating ribosome affinity purification (TRAP) technique to map the translatomes of excitatory glutamatergic (vGluT2+) and inhibitory GABA and/or glycinergic (vGAT+ or Gad67+) neurons of the mouse spinal cord. Our analyses demonstrate that inhibitory and excitatory neurons are not only set apart, as expected, by the expression of genes related to the production, release or re-uptake of their principal neurotransmitters and by genes encoding for transcription factors, but also by a differential engagement of neuromodulator, especially neuropeptide, signaling pathways. Subsequent multiplex in situ hybridization revealed eleven neuropeptide genes that are strongly enriched in excitatory dorsal horn neurons and display largely non-overlapping expression patterns closely adhering to the laminar and presumably also functional organization of the spinal cord grey matter.